The Actualities And Development Of Electronic Commerce In China - Wenlong, Qi (2008)
Electronic commerce refers to commercial activities backed by computer network. It is a burgeoning and vigorous commercial activity in China.In general, with the joint endeavor of both the Chinese government and the scientific talents, substantial achievement has been made in the development of China's Electronic Commerce, and in the near future, China's Electronic Commerce will be further perfected.